Leisure Time 1957−1967: Contemporary Discussions and Defi nitions - Franc, Martin; Knapík, Jiří (Dějiny – teorie – kritika, 2012)
Th e authors analyse the contemporary sociological discussion on the subject of leisure time and non-occupational activities in Czechoslovakia in the second half on 1950s and in the 1960s. They reflect upon the limitations of the then existing understanding of free time in Czechoslovakia and confront the view of Czech sociologists with contemporary views of sociologists from countries of both the Eastern Bloc and West-European environment. Authors conclude that in Czechoslovakia, especially the views of contemporary French sociology of free time were to a surprising degree known and debated. Attention is also paid to numerous contemporary empirical research projects. Authors then address the question to what extent this empirical research was reflected in the general principles of understanding of leisure time, in adjustments to working hours, as well as in attempts at qualitative improvement of daily life.